## If x² – kx – 6 = (x – 6) (x + 1) forall x, then the value of k is​

Question

If x² – kx – 6 = (x – 6) (x + 1) forall x, then the value of k is​

in progress 0
2 months 2021-07-30T03:59:42+00:00 2 Answers 0 views 0

Step by step explanation:-

Given:

x²-kx-6= (x-6)(x+1)

To find:

we have to find the value of x

x²-kx-6= (x-6)(x+1)

Firstly expanding the terms and opening the brackets on the LHS

=> x²-kx-6= x( x+1)-6(x+1)

=> x²-kx-6= x²+x-6x-6

=> x²-kx-6= x²-5x-6

Both sides quadratic equation is formed .

Both side LHS and RHS which are same cancel it,

x² and x and -6 become cancel

after comparing,we get -k= -5

than minus minus both side cancel

k= 5

Check

x²-kx-6

=>x²-5x-6 which is equal to the RHS

2. ## Given

x²-kx-6= (x-6)(x+1)

## To find

we have to find the value of x

x²-kx-6= (x-6)(x+1)

Firstly expanding the terms and opening the brackets on the LHS

=> x²-kx-6= x( x+1)-6(x+1)

=> x²-kx-6= x²+x-6x-6

=> x²-kx-6= x²-5x-6

we see on both sides quadratic equation is formed .

Now , comparing the coefficient of x on both sides because we have to find the value of x and on the right side k is the coefficient of x.

after comparing,we get -k= -5

## Check

x²-kx-6

=>x²-5x-6 which is equal to the RHS